2022
DOI: 10.1292/jvms.22-0026
|View full text |Cite
|
Sign up to set email alerts
|

G and P genotype profiles of rotavirus a field strains circulating in a vaccinated bovine farm as parameters for assessing biosecurity level

Abstract: After improvement of hygiene protocols on boots in a bovine operation (farm A) in Ibaraki, Japan in September 2017, mortality of calves and the detection of 4 viral pathogen indicators, including bovine rotavirus A (RVA), became significantly low for one year. Subsequently, in the present study, these indicators and mortality were monitored and confirmed all were still low, except for the detection rate of bovine RVA in calves less than 3 weeks old. The present study aimed to investigate G and P genotypic prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…In the present study, the bovine genotypes (VP7) G2, G6, G8, G10, and P (VP4) P [1], P [2], P [4], P [6], and P [11] were identified. These results coincide with findings detected in Costa Rica [1], Brazil [12,13], Uruguay [14] Argentina [15], and other countries of the world [12,16], where high frequencies of these genotypes are reported, considered, as well as, frequent and of epidemiological importance in cattle and pigs.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, the bovine genotypes (VP7) G2, G6, G8, G10, and P (VP4) P [1], P [2], P [4], P [6], and P [11] were identified. These results coincide with findings detected in Costa Rica [1], Brazil [12,13], Uruguay [14] Argentina [15], and other countries of the world [12,16], where high frequencies of these genotypes are reported, considered, as well as, frequent and of epidemiological importance in cattle and pigs.…”
Section: Introductionsupporting
confidence: 90%
“…Concerning the G10 P [1] genotype detected in Panama, it differs from that reported for bovine rotavirus in Latin America; however, regarding bovine rotavirus infections G6, G8, and G10 together with P [1], P [5], and P [11], respectively, are the G and P genotypes most commonly found [17]. Other investigations show detection of this same combination in goats and lambs in Bangladesh [18,19]; genotype P [1] has also been detected in cattle in Japan [16]. It is…”
Section: Introductionmentioning
confidence: 92%
“…In the presence of organic matter such as litter and feces, disinfectants required more time to inactivate viruses and became less effective, suggesting that a cleaning step is important before disinfection [ 1 ]. In our previous reports, it was demonstrated that changing boots at the entrance of each calf shed and performing appropriate foot baths after boot use inside the shed results in lowered virus detection rates and lowered mortality rates [ 19 , 21 ]. These results suggested that changing boots and clothes is necessary for preventing pathogens from entering the hygiene management area.…”
Section: Discussionmentioning
confidence: 99%
“…Changing personal protective equipment (clothing and footwear) could prevent transmission of porcine epidemic diarrhea (PED) virus to sentinel pigs as a result of biosecurity procedures [ 20 ]. In September 2017, improved hygiene standards on boots in a bovine operation (farm A) in Ibaraki, Japan resulted in a significant reduction in both calf mortality and detection of four viral pathogen indicators for two years, except for the detection rate of bovine RVA in calves less than 3 weeks old [ 19 , 21 ]. In December 2019, the protocols for boots hygiene were revised on farm A ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from Japan investigated the G and P genotypic profiles of BoRVAs on a farm from 2018 to 2020 [ 27 ]. Molecular analysis of positive RVAs ( n = 122) using semi-nested multiplex RT-PCR, followed by sequencing of selected samples, identified G6, G8, G10, P[1], P[5], and P[11] [ 27 ].…”
Section: Discussionmentioning
confidence: 99%